1989
DOI: 10.1677/joe.0.1210545
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood levels of immunoreactive inhibin during pseudopregnancy, pregnancy and lactation in the rat

Abstract: Concentrations of inhibin in peripheral blood were determined by radioimmunoassay in pseudopregnant, pregnant and lactating rats and correlated with the status of follicular development, luteal function in the ovaries and placental function. In pseudopregnant rats, plasma concentrations of inhibin remained relatively high from days 2 to 12 of pseudopregnancy and no significant changes occurred throughout pseudopregnancy. In pregnant rats, a marked decline in plasma concentrations of inhibin occurred between da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Previous studies (Kishi et al 1995, Ohshima et al 1999) also demonstrated that the changing pattern of plasma concentrations of inhibin corresponded well with the number of healthy large antral follicles during the oestrous cycle. Similar correlations of inhibin and follicular development have also been observed in female rats in the various reproductive stages (Taya et al 1989). In the present study, after ovariectomy but not after hysterectomy or placentectomy, plasma concentrations of inhibin A and inhibin B decreased abruptly.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies (Kishi et al 1995, Ohshima et al 1999) also demonstrated that the changing pattern of plasma concentrations of inhibin corresponded well with the number of healthy large antral follicles during the oestrous cycle. Similar correlations of inhibin and follicular development have also been observed in female rats in the various reproductive stages (Taya et al 1989). In the present study, after ovariectomy but not after hysterectomy or placentectomy, plasma concentrations of inhibin A and inhibin B decreased abruptly.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the present study, together with those of our previous study [22], therefore, suggest that basal levels of LH are essential for follicular maintenance and secretion of inhibins and estradiol-17β during the second half of pregnancy in the golden hamster. Supporting the present study, tonic secretion of LH play an important role in the regulation of follicular development during the various reproductive stages in the rat [9,[23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 83%
“…Dev. 43: [279][280][281][282][283][284][285][286][287] 1997) ntral follicles usually exist in the ovary during pseudopregnancy of the rat, although plasma reported previously [4,5]. A specific surge of FSH is not essential for the recruitment and development of a new set of follicles in cyclic rats [6].…”
mentioning
confidence: 99%